Remoção de sementes por formigas sob diferentes perspectivas comunidade identidade de espécies e ambiente - Rabelo, Mariana Azevedo (2017)
The dispersion of diaspores by ants is an important ecological function that contributes to the maintenance of ecosystems, by promoting the establishment of plant species in more appropriate places and contributing to the nutrition of the colonies and consequently benefit other ecological groups. For these reasons, the seed removal by ants can contribute to the maintenance of natural environments and the recovery and restoration of areas impacted by natural or anthropic processes. However, little is known about which variables influence seed removal from different perspectives such as: community, species identity and environment. Thus, the present study sought to evaluate the seed removal rate from three perspectives: community of ants (distance and number of nests in relation to the food resource - seeds), identity of the species (identity of the ants species, removal timing, and distance from the nests), and environment (proportion of canopy shading and leaf litter cover on the ground). The study was carried out in 15 cerrado sensu stricto areas, belonging to the Environmental Protection Area of Rio Pandeiros, northern Minas Gerais. In these areas we measured the distance traveled by ants from the food resource to their nests, quantified the nests of the ants, the shading proportions caused by the canopy and leaf litter cover in the soil, the time of removal of the seeds to the nests and identification of ants species. A total of 42 nests were identified, ranging from 0.35 to 15.32 m from the artificial seeds, belonging to 11 species of ants. Regarding to the variables related to the three perspectives, the distance of the nests was the only one that influenced the rate of seed removal, but only from the perspective of the removal species. Thus, our study demonstrated that a variable can influence the seed removal depending on the perspective, which highlights the importance of a holistic assessment of the aspects related to community, species identity and environment that can contribute to the success of ant removal. This information contributes to the advancement of the knowledge of seed removal by ants, and can improve conservation projects, monitoring or restoration of areas.